The receptor for advanced glycation end-products: A complex signaling scenario for a promiscuous receptor - Rojas, Armando (2017)
Firstly described in 1992, the receptor for advanced glycation end-products has attracted increasing attention due to its diverse ligand repertoire and involvement in several pathophysiological processes associated with inflammation such as in diabetes, cancer, autoimmune diseases and neurodegenerative diseases. This receptor in addition to its binding capacity for advanced glycation end-products also recognizes some molecules classified as both, pathogen- and damage-associated molecular patterns and thus triggering the transcription of genes encoding inflammatory mediators. Some of these ligands are common for both, the receptor of advanced glycation end-products and members of the Toll-like receptor family, generating shared signaling cascades. Furthermore, these receptors may cooperate as essential partners through the recruitment and assembly of homo- and hetero-oligomers in order to strengthen the inflammatory response. The purpose of this review is to highlight the importance of some particular features of this multiligand receptor, its signaling cascade as well as the cross-talk with some members of the Toll-like receptor family.